Absolute counts of leukocyte subsets in peripheral blood in pregnancies complicated by preterm prelabour rupture of membranes - Soucek, Ondrej; Kacerovsky, Marian; Kacerovska Musilova, Ivana; Stranik, Jaroslav; Kukla, Rudolf; Bolehovska, Radka; Andrys, Ctirad (Journal of obstetrics and gynaecology : the journal of the Institute of Obstetrics and Gynaecology, 2024)
BACKGROUND: This study aimed to assess variations in the absolute counts of various leukocyte subsets in the peripheral blood of women with pregnancies affected by preterm prelabour rupture of membranes (PPROM), in relation to the presence of intra-amniotic inflammation (IAI). METHODS: The study included fifty-two women with singleton pregnancies experiencing PPROM. Absolute counts of different leukocyte subpopulations, such as granulocytes, monocytes, lymphocytes, T cells and their subsets, B cells and their subsets, and NK cells and their subsets, were measured in maternal peripheral blood samples using multicolour flow cytometry. IAI was identified by elevated concentrations of interleukin 6 (IL-6) in the amniotic fluid, which was collected through transabdominal amniocentesis. RESULTS: Women with IAI exhibited higher absolute counts of leukocytes (p = 0.003), granulocytes (p = 0.008), and monocytes (p = 0.009). However, the presence of IAI did not significantly affect the absolute counts of lymphocytes or their subpopulations. CONCLUSIONS: The study found that IAI is associated with changes in the absolute counts of leukocytes from the innate immunity compartment in the peripheral blood of women with pregnancies complicated by PPROM. Conversely, it does not significantly alter the counts of cells from the adaptive immune system. The changes observed may reflect the natural, temporal, and localised characteristics of IAI.
Keywords: těhotenství; přirozená imunita; Interleukin-6; Amniotic Fluid; lidé; průtoková cytometrie; Adult; předčasný odtok plodové vody; Female; plodová voda; Flow Cytometry; Immunity, Innate; Humans; interleukin-6; Fetal Membranes, Premature Rupture; chorioamnionitida; amniocentéza; Leukocyte Count; Pregnancy; ženské pohlaví; Chorioamnionitis; Leukocytes; leukocyty; dospělí; Amniocentesis; počet leukocytů